Biological control of Pyricularia oryzae, using fungal metabolites - Idan, Ali Abdulameer (2017)
Rice blast caused by fungus Pyricularia oryzea is one of the most devastating among rice diseases. The disease has been classified as one of the most serious diseases that influence the production of rice since rice fields are seriously damaged, thereby affecting yield and quality. To decrease the use of pesticides, biological control is considered as an alternative sustainable control. Aspergillus spp. has been widely found to be useful in biotechnology as a bio control agent. They have a high ability in the production of secondary metabolites. Aspergillus spp. was obtained from the rice field soil located in Selangor, Tanjung Karang, Peninsular Malaysia. Isolates UPMZ01 and UPMZ02 were screened against blast pathogen by applying dual culture technique. The antagonism of isolate UPMZ01 was (81.326%) while UPMZ02 gave (70.9%) of inhibition percentage against P. oryzae. Culture filtrate was also used to screen the inhibitory effect against the pathogen. The results revealed that isolate UPMZ01 gave the optimum inhibitory percentage of (100%) at all concentrations of fungal secondary metabolites at 14 days. Based on ITS sequencing, the isolate UPMZ01 was identified as Aspergillus niger and UPMZ02 as Aspergillus flavus. The environmental factors such as pH and temperature influenced the production of secondary metabolites. The optimum condition for A. niger to produce efficient antifungal metabolites that gave (100%) PIGR against blast pathogen was at pH 5.0 and 21 to 29ºC. The secondary metabolites compounds were identified by gas chromatography-mass spectrometry (GC-MS). Fifteen compounds were recognized as major compounds. The identified compounds were Oleic Acid, n-Hexadecanoic acid, Hexose, Glycerol, Stearic acid, Tetradecanoic acid, Dodecanoic acid and 5-Hydrxoymethylfurfural. The Liquid chromatography-mass spectrophotometry (LC-MS/MS) analysis revealed four compounds, Succinic acid, Al21 anion, Diphenylarsine and N-Acetylaspartic acid. However, the culture filtrate of A. niger UPMZ01 may contribute to control rice blast pathogen.